Collaborative approaches to SDGs: Catalyzing sustainability in food, energy, and water security - Jolius, Gimbun; Siti Kholijah, Abdul Mudalip; Mohd Sabri, Mahmud; Agi, Augustine Aja; Nurul Aini, Mohamed Razali (IOP Publishing, 2025)
This paper is a preface to the proceedings of the 7th International Conference of Chemical Engineering and Industrial Biotechnology, which was held in The Everly Hotel, in Putrajaya, Malaysia, on August 27-29, 2024. A wide-ranging discussion on the Food-Water-Energy Nexus took place during the conference, specifically in the track session on water and environment, food and pharmaceuticals, as well as bioenergy and renewable energy.